Evaluating the content of the English book for the third grade secondary in Saudi Arabia in light of the future skills - Al-Tamimi, Lama Abdullah; Abu Saleem, Eman Hussain (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to evaluate the content of the English book of the third grade secondary in the light of future skills, and the researcher used the mixed curriculum that combined the analytical descriptive curriculum, relying on the content analysis card as a study tool, and the qualitative curriculum based on the focus group tool. The study community consisted of English textbooks for the third grade secondary in Saudi Arabia, and English teachers and supervisors for the third grade secondary in government schools in Al-kharj.The results showed that the degree of inclusion of Future skills came to varying degrees: the higher thinking skills was the highest in inclusion in book content. followed by social and emotional skills at a moderate level, while the practical skills came at the last level. The study presented proposals for the development of the content of the English book of the third grade in the light of future skills, including the development of the nature of the applied activities of the content, so as to transform forms related to linguistic application in situations of the reality of society, its problems and the student's life, allowing for the support of future skills.
Keywords: Content Calendar; English Language Book; Future Skills